Respostas

A melhor resposta!
2013-12-07T23:58:41-02:00
10 + x = 9 - 2x
x + 2x = 9 - 10
3x = - 1
x = - 1 : 3
x = - 1/3

0,3 (x - 1) + 0,4 (x - 2) = 7
0,3x - 0,3 + 0,4x - 0,8 = 7
0,3x + 0,4x = 7 + 0,3 + 0,8
0,7x = 8,1
x = 8,1 : 0,7
x = 8,1/0,7
1 5 1
  • Usuário do Brainly
2013-12-08T00:11:50-02:00

10 + x = 9 - 2x

+ x + 2x = 9 - 10

+ 3x = - 1

x = - 1 : 3

x = 0,333333333333333333333333333333333333333...


0,3 (x - 1) + 0,4 (x - 2) = 7

0,3x - 0,3 + 0,4x - 0,8 = 7

0,3x + 0,4x = 7 + 0,3 + 0,8

0,7x = 8,1

x = 8,1 : 0,7

x = 11,57142857...